Flow and performance characteristics of a Y-shaped diffusing duct using CFD. (6th January 2011) - Anand, R.B.; Chandraprabhu, A.; Richards, X.J.A.; Hareshram, N.
A computational investigation is carried out to study the flow and performance characteristics of a Y-shaped diffusing duct having two inlets and one outlet with an overall area ratio of 2 using a commercial CFD code, FLUENT. The CFD code is validated with the experimental results and it was found that the code applying the RNG k-e turbulence model has the capability of predicting the flow and performance characteristics for the similar geometry. The Y-shaped diffusing duct is formed by merging two symmetrical S-shaped diffusing ducts (area ratio = 4, curvilinear length = 600 mm, angle of turn = 22.5°/22.5°) at the centreline of outlet. The flow and performance characteristics of the duct are analysed for a uniform flow profile at the inlet that is observed in the experiments. The results are presented in the form of contour plots for the axial velocity distribution and the cross-flow velocity distribution in terms of vector plots. The analysis reveals the fact that however the flow at the diffuser inlet is uniform, secondary flows are induced as an effect of curvature and change in the cross-sectional area.